Overview of the Epizootiological Situation on Highly Pathogenic Avian Influenza in Russia in 2020 - V. Yu. Marchenko; N. I. Goncharova; E. V. Gavrilova; R. A. Maksyutov; A. B. Ryzhikov (Проблемы особо опасных инфекций, 2021)
This review describes the current situation on highly pathogenic avian influenza virus in 2020 and provides forecast of the possible further spread of avian influenza in Russia. In 2020, the circulation of a wide variety of highly pathogenic avian influenza virus subtypes which have epizootiological and epidemiological significance was recorded in the world. Outbreaks of highly pathogenic avian influenza were reported in over 30 countries. Apart from this, human infections with influenza viruses of the A/H5Nx and A/H9N2 subtypes were reported. There was a large-scale epizootic in Russia in 2020, which affected more than 10 regions. Outbreaks among wild birds and poultry were caused by the highly pathogenic influenza virus A/H5N8 of clade 2.3.4.4b. As a result of those outbreaks, more than 1.5 mil. poultry were killed or perished. It was revealed that strains of the influenza virus isolated in Russia have a high degree of identity with the strains circulating in Europe and Southeast Asia. Thus, it was shown again that the territory of Russia plays an important role in the global spread of avian influenza virus.